Intentional Exposure to Extreme Cold Temperature to Influence Shape and/or Weight and Its Association to Eating Disorder Pathology - Reas, Deborah Lynn; Dahlgren Lindvall, Camilla; Wonderlich, Joseph; Rø, Øyvind (Frontiers in Psychology, 2019)
Very little is known about potentially dangerous forms of weight control or compensatory behaviors involving deliberately exposing oneself to cold temperature. We investigated frequency of intentional cold exposure behavior to influence shape/weight and its relation to eating disorder pathology. Participants (496; 94.0% females) were recruited via print advertisements and social media. Items were based on a review of scientific literature, popular media, pro-ED forums, and input from clinicians and persons with a lived experience. Lifetime cold exposure and frequency during the past 28 days (“never” to “very often”) were assessed. Participants completed a new self-report questionnaire (Intentional Cold Exposure-Questionnaire; ICE-Q) and measures of eating pathology. Approximately 1/2 of individuals with a current ED had engaged in at least one type of cold exposure behavior during the past 28 days versus 17% of individuals without an ED, although average frequency was low. Common cold exposure behaviours included underdressing, turning down the heat, ingesting ice-cold beverages, and ice baths. Significant moderate correlations existed between the ICE-Q and measures of ED pathology. This is the first study to assess intentional exposure to cold temperature as a means of controlling shape and/or weight. Cold exposure does not appear to be socially normative as a weight control method, but a markedly pathological behavior associated with ED symptomology. Findings indicate a propensity towards experimentation, but sporadic uptake, of cold exposure by individuals with a ED. Future research is needed to assess replicability and to investigate the clinical, theoretical, and prognostic significance of deliberate cold exposure behavior.